2011
DOI: 10.1029/2010gl046019
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between plasma escape and the Martian crustal magnetic field

Abstract: [1] Data from ASPERA-3 on Mars Express is used to study the geographic distribution of ionospheric O + outflow and escape from Mars. Of particular interest is how the ion outflow relates to the crustal magnetic field regions facing the dayside, flank, and nightside of Mars. The most intense O + fluxes are generated on the dayside at altitudes below ≈1000 km, peaking over the southern hemisphere in the longitude sector 120°-250°. This sector coincides with the strongest crustal magnetic field regions at Mars. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 16 publications
3
65
1
Order By: Relevance
“…Possible sources of asymmetry which could affect our estimate include uneven sampling of the northern and southern hemisphere, and uneven sampling relative to the direction of the solar wind electric field. In Lundin et al (2011) it was shown that the tail fluxes show no hemispheric asymmetry, so this would not affect our results. Nilsson et al (2011) showed that there are flow asymmetries with more escape from the north and dusk as compared to south and dawn.…”
Section: Trans-terminator Flowmentioning
confidence: 78%
See 1 more Smart Citation
“…Possible sources of asymmetry which could affect our estimate include uneven sampling of the northern and southern hemisphere, and uneven sampling relative to the direction of the solar wind electric field. In Lundin et al (2011) it was shown that the tail fluxes show no hemispheric asymmetry, so this would not affect our results. Nilsson et al (2011) showed that there are flow asymmetries with more escape from the north and dusk as compared to south and dawn.…”
Section: Trans-terminator Flowmentioning
confidence: 78%
“…The influence of magnetic anomalies on ion distributions have also been studied, e.g. Lundin et al (2011) and Nilsson et al (2006aNilsson et al ( , 2011, finding that the magnetic anomalies does affect the ion fluxes in the vicinity of the planet, but does not cause a hemispheric asymmetry of the escape inside the nominal IMB. The escape from the dayside ionosphere and/or pick up ion fluxes are larger from the northern hemisphere, which have less magnetic anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…The mean fluxes of cold and low energy (E i ≤ 50 eV) ionospheric oxygen ions are plotted as a function of the same variables. The observed upward lifting of oxygen ions in the regions with strong crustal magnetization can be responsible for a significant asymmetry of the upper ionosphere (see also Lundin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On the observational side, there is on one hand no clear evidence that magnetic anomalies actually have a significant influence on the solar wind ion dynamics in the nearMars environment (Diéval et al, submitted, 2011;Stenberg et al, 2011). On the other hand, there is evidence that in the Southern hemisphere, the strong magnetic anomalies reduce the ionospheric ion outflow (Nilsson et al, 2011) and affect the flow pattern of escaping O + ions (Lundin et al, 2011). The possible effect of the magnetic anomalies on proton precipitation will be investigated in a future statistical study using Mars Express observations.…”
Section: Modelmentioning
confidence: 99%